Control of filariasis vector using Ovillanta in Gwale local Government area of Kano State, Nigeria - Umar, A. B.; Dankaka, A. H.; Shah, M. Manjur (Journal of Ecobiotechnology, 2020)
The study was aimed at finding the effectiveness of a physical method of controlling filariasis vector larvae. Four ovillanta traps were placed in four different sites (north, south, west and east) of Gwale Local Government area of Kano state. The eggs and immature stage(larvae) of the filariasis vector were collected and destroyed. A total of 134667 larvae were collected altogether. 25% from site A, 23% from site B, 28% from site C and 24% from site D.The finding of the study shows that ovillanta trap is an effective method in controlling filariasis vector.